Switzerland : 2003 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report, 2003)
This 2003 Article IV Consultation highlights that following a solid expansion in 1997-2000, economic growth in Switzerland is currently stalled as exports have been hurt by the global slowdown and domestic investment has undergone a sharp downward correction from earlier high levels. The important financial sector has been hit particularly hard, in part because of the steep declines in equity prices both in Switzerland and abroad. Unemployment has doubled, although it remains low by international standards. Inflation is negligible, and the external current account is running a large surplus.